Applying current normative data to prognosis in heart failure: The Fitness Registry and the Importance of Exercise National Database (FRIEND). (15th July 2018) - Moneghetti, Kegan J.; Hock, Julia; Kaminsky, Leonard; Arena, Ross; Lui, George K.; Haddad, Francois; Wheeler, Matthew; Froelicher, Victor; Ashley, Euan; Myers, Jonathan; Christle, Jeffrey W.
Abstract: Introduction: Percent of predicted peak VO2 (ppVO2 ) is considered a standard measure for establishing disease severity, however, there are known limitations to traditional normative values. This study sought to compare ppVO2 from the newly derived "F itnessR egistry and theI mportance ofE xercise: aN ationalD atabase" (FRIEND) registry equation to conventional prediction equations in a clinical cohort of patients undergoing cardiopulmonary exercise testing (CPX). Methods and results: We selected 1094 patients referred for evaluation of heart failure (HF) symptoms who underwent CPX. ppVO2 was calculated using the FRIEND, Wasserman/Hansen and Jones equations. Participants were followed for a median of 4.5 years [Interquartile range 3.5–6.0] for the composite endpoint of death, advanced HF therapy, or acute decompensated HF requiring hospital admission. Mean age was 48 ± 15 years and 62% were female. The FRIEND registry equation predicted the lowest ppVO2 (measured/predicted; 71 ± 31%), compared to the Wasserman/Hansen (74 ± 29%) and Jones equations (83 ± 33%) ( p  < 0.001). All expressions of peak VO2 were significant as univariate predictors of outcome with no significant differences between equations on pairwise analysis of receiver operating characteristic curves. When compared at a similar threshold of ppVO2 the event rate was significantly lower in the FRIEND registry equation versus the currently used Wasserman and Jones equations. Conclusion: The use of the newly derived FRIEND registry equation predicts HF outcomes; however, it appears to predict a higher predicted VO2 ; the clinical implication being a lower threshold of percent predicted peak VO2 should be considered when risk stratifying patients with HF. Highlights: There appears to be significant differences between values of predicted VO2 derived from contemporary equations. Percent of predicted peak VO2 derived from the FRIEND registry equation strongly predicts heart failure outcomes. Percent of predicted VO2 derived from the FRIEND registry equation below 70% represents patients at higher risk of heart failure outcomes.